A composite material of modified artificial graphite and carbon-coated graphite and its preparation process

Through the composite material and preparation process of modified artificial graphite and carbon graphic graphite, the problem of lack of performance when the lithium -ion battery negative electrode material is used in one use, and the high -cycle stability and fast charge adaptability of the battery are realized.

CN118888727BActive Publication Date: 2025-01-28ZAOZHUANG HIGH ENERGY NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410989804.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2025-01-28
Estimated Expiration
2044-07-23

AI Technical Summary

Technical Problem

When the existing lithium-ion battery negative electrode active materials are used alone, their performance has their own advantages and disadvantages, and it is difficult to effectively synergize the advantages of both.

Method used

The composite materials and preparation processes of modified artificial graphite and carbon covering graphite are used to form a composite material with a D50 to 15-20 μm through the steps such as ultrasonic dispersion, acid peroxide solution oxidation, carbonization, and shear pinch.

Benefits of technology

Improve the infiltration capacity of the electrolyte and the cycle stability of the battery, enhance the ability and electrolyte utilization efficiency of the battery in the fast charging system, and extend the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of secondary battery material preparation, and more specifically, relates to a composite material of modified artificial graphite and carbon-coated graphite and a preparation process thereof. The preparation process comprises the following preparation steps: modification of artificial graphite: after artificial graphite is ultrasonically dispersed and peeled, an acidic hydrogen peroxide solution is added for oxidation to form oxygen-containing functional groups on the surface of artificial graphite, and particles with a D50 of 5-10 μm are screened out to obtain modified artificial graphite; carbon coating of natural graphite: natural graphite, asphalt and microcrystalline cellulose are blended, carbonized, crushed, and particles with a D50 of 100-300 nm are screened out to obtain carbon-coated graphite; composite material preparation: by weight, 4-6 parts of polytetrafluoroethylene resin, 8-10 parts of N-methylpyrrolidone, 25-30 parts of carbon-coated graphite, and 120-150 parts of modified artificial graphite are taken, mixed, sheared and kneaded to obtain a kneaded material; the kneaded material is heated to 720-800°C in an oxygen-free environment for carbonization, and then crushed and screened to obtain a composite material with a D50 of 15-20 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary battery material preparation, and more specifically, relates to a composite material of modified artificial graphite and carbon-coated graphite and a preparation process thereof. Background Art

[0002] When natural graphite and artificial graphite are used as negative electrode active materials for lithium-ion batteries, each has its own advantages and disadvantages. Specifically, natural graphite has a higher theoretical capacity (340-370mAh / g); while artificial graphite is relatively lower (310-360mAh / g); compared with artificial graphite, natural graphite has abundant material sources and does not need to undergo the high-temperature graphitization process of carbon materials. Therefore, its cost advantage is obvious; however, natural graphite itself has many defects, and its cycle stability is obviously not as good as artificial graphite; in particular, the expansion rate of natural graphite is higher when in use, while that of artificial graphite is relatively lower. Summary of the invention

[0003] The technical problem to be solved by the present invention is that when artificial graphite or natural graphite is used alone as the negative electrode active material of the existing lithium ion battery, the performance of the two has their own advantages and disadvantages, and simply directly blending the two is difficult to effectively synergize the advantages of the two. A composite material of modified artificial graphite and carbon-coated graphite and a preparation process thereof are provided.

[0004] The purpose of the present invention is to provide a composite material of modified artificial graphite and carbon-coated graphite.

[0005] Another object of the present invention is to provide a process for preparing a composite material of modified artificial graphite and carbon-coated graphite.

[0006] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0007] A composite material preparation process of modified artificial graphite and carbon-coated graphite, the specific preparation process comprising:

[0008] Artificial graphite modification:

[0009] After the artificial graphite is ultrasonically dispersed and exfoliated, an acidic hydrogen peroxide solution is added for oxidation to form oxygen-containing functional groups on the surface of the artificial graphite, and then particles with a D50 of 5-10 μm are screened out to obtain modified artificial graphite;

[0010] Carbon coating of natural graphite:

[0011] Natural graphite, asphalt and microcrystalline cellulose are blended, carbonized, crushed, and sieved to obtain particles with a D50 of 100-300 nm to obtain carbon-coated graphite;

[0012] Composite material preparation:

[0013] By weight, 4-6 parts of polytetrafluoroethylene resin, 8-10 parts of N-methylpyrrolidone, 25-30 parts of carbon-coated graphite, and 120-150 parts of modified artificial graphite are mixed, sheared and kneaded to obtain a kneaded material;

[0014] The kneaded material is heated to 720-800°C in an oxygen-free environment for carbonization, and then crushed and sieved to obtain a composite material with a D50 of 15-20 μm.

[0015] Firstly, an acidic hydrogen peroxide solution is used to oxidize the artificial graphite after ultrasonic exfoliation, so that the surface and edge of the artificial graphite sheet structure are oxidized and oxygen-containing functional groups are formed, thereby improving its surface activity, thereby improving the wetting ability of the electrolyte to it, especially, when it is used as the core, the affinity of the functional groups to the electrolyte can still be used to make the electrolyte easily penetrate; secondly, asphalt and microcrystalline cellulose are blended as the surface coating layer of natural graphite, and the asphalt acts as a direct bridge between microcrystalline cellulose and natural graphite before the initial carbonization. During the carbonization process, both microcrystalline cellulose and asphalt are carbonized, among which the microcrystalline cellulose retains its fibrous structure during the carbonization process, which is conducive to the formation of a "fluffy" coating layer on the surface of natural graphite, by changing its surface physical structure. , which improves the "chemical inertness" of its surface to the electrolyte, allowing the electrolyte to infiltrate smoothly while making it difficult for the electrolyte to be consumed due to side reactions caused by direct contact with the rich functional groups on the surface of natural graphite; finally, small particles of carbon-coated natural graphite are used to coat large particles of modified artificial graphite. In this way, the excellent ionic conductivity of the natural graphite after carbon coating can be utilized to quickly absorb the lithium ions that migrate to the negative electrode during the charging process, while the large particles of artificial graphite serve as the basic core, and the oxygen-containing functional groups formed by its oxidation and the oxygen-containing functional groups in the natural graphite of the coating layer are chemically bonded during the carbonization process, thereby constructing a strong core-shell structure, so that the product can adapt to the fast charging system, and at the same time the physical structure is stable, and the infiltration of the electrolyte from the outside to the inside will also become easier.

[0016] Furthermore, the ultrasonic dispersion peeling comprises:

[0017] Artificial graphite and water are mixed in a mass ratio of 1:8, and then 1-3% of the mass of artificial graphite sodium lignin sulfonate is added, followed by continuous ultrasonic dispersion for 2-3 hours at a temperature of 80-90° C. and an ultrasonic frequency of 180-200 kHz to obtain a dispersion.

[0018] Through temperature, high ultrasonic power, and the use of dispersant sodium lignin sulfonate, the interlayer spacing in the artificial graphite sheet structure is widened, which is conducive to the easy exposure of defects in its structure, thereby facilitating the smooth introduction of oxygen-containing functional groups at the defects during the subsequent oxidation reaction.

[0019] Further, the adding of an acidic hydrogen peroxide solution for oxidation comprises:

[0020] Add 0.8-1.2 times the mass of the dispersion liquid in an acidic hydrogen peroxide solution to the dispersion liquid, and then stir and react for 4-6 hours at a temperature of 70-75°C and a stirring speed of 800-1000 r / min;

[0021] Wherein, in the acidic hydrogen peroxide solution, the mass fraction of sulfuric acid is 10-15%, and the mass fraction of hydrogen peroxide is 20-25%.

[0022] By reasonably controlling the concentration of raw materials and reaction process parameters during the oxidation reaction, the number of oxygen-containing functional groups introduced on the surface of artificial graphite can be controlled. If the oxidation is excessive, the surface energy of the artificial graphite will be too high, and it will be difficult to form a uniform mixture with other components during the subsequent kneading process. If too few oxygen-containing functional groups are introduced on the surface, only very few oxygen-containing functional groups will remain after being consumed during the carbonization process, and their effect on improving the wetting between the inner core and the electrolyte will be very limited.

[0023] Furthermore, when the natural graphite is carbon-coated, the mass ratio of the natural graphite, the asphalt and the microcrystalline cellulose is (80-90):(10-12):(1-3).

[0024] When using microcrystalline cellulose, its dosage must be considered. If the dosage is too low, it will be difficult to form a sufficient and relatively evenly distributed fluffy coating on the surface of natural graphite, which will make it difficult for the electrolyte to infiltrate. If the dosage is too high, it will easily lead to an increase in the diffusion resistance of lithium ions on the surface of natural graphite, which will be detrimental to the fast charging capability of the product.

[0025] Furthermore, when the natural graphite is carbon-coated, 0.6-0.8% of the mass of the natural graphite is added with boehmite, and the D50 of the boehmite is 100-150nm.

[0026] The inventors found that after solving the organic synergy between artificial graphite and natural graphite, in the later stage of the product cycle, after the electrolyte is gradually consumed, the inside of the battery is in a lean state. At this time, it will be difficult for the negative electrode material to fully utilize the "poor" electrolyte. However, if a certain amount of boehmite is added when the natural graphite is coated, this problem can be significantly improved. The specific reasons are: first, the hardness of boehmite is lower than that of alumina, and it will not cause damage to the physical structure of the graphite material during the product preparation process. Secondly, it can be dehydrated and converted into stable alumina during the high-temperature carbonization process. The gases generated during the dehydration process and the carbonization process can form certain pores around it. In this way, the position where the alumina exists has a better liquid holding capacity, thereby improving the product's utilization of the electrolyte in the lean state, and further improving the product's cycle life.

[0027] Furthermore, the asphalt is selected from any one of coal asphalt and petroleum asphalt.

[0028] Furthermore, the shearing and kneading comprises: in a kneading machine, at a rotation speed of 220-260 r / min and a temperature of 65-70° C., continuously shearing and kneading for 6-8 hours.

[0029] A composite material of modified artificial graphite and carbon-coated graphite is prepared by the preparation process. DETAILED DESCRIPTION

[0030] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0031] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0032] Example 1

[0033] Artificial graphite modification:

[0034] Artificial graphite and water were mixed in a mass ratio of 1:8, and then 1% of the mass of artificial graphite sodium lignin sulfonate was added, followed by constant temperature ultrasonic dispersion for 2 hours at a temperature of 80°C and an ultrasonic frequency of 180kHz to obtain a dispersion;

[0035] The obtained dispersion was transferred into a reactor, and an acidic hydrogen peroxide solution of 0.8 times the mass of the dispersion was added into the reactor, and then the reactor was closed, and the reaction was stirred at a constant temperature of 70°C and a stirring speed of 800 r / min for 4 hours, and then the filter cake was collected and washed with deionized water until the washing liquid was neutral, and the washed filter cake was transferred into a drying oven and dried to constant weight at a temperature of 100°C to obtain a dry filter cake;

[0036] The dried filter cake was manually ground in a mortar for 20 min, and then sieved to separate particles with a D50 of 5 μm to obtain modified artificial graphite;

[0037] Wherein, in the acidic hydrogen peroxide solution, the mass fraction of sulfuric acid is 10%, and the mass fraction of hydrogen peroxide is 20%;

[0038] Carbon coating of natural graphite:

[0039] According to the mass ratio of natural graphite, asphalt and microcrystalline cellulose of 80:10:1, the three raw materials are weighed respectively, and the three raw materials are poured into a ball mill, and then 0.6% boehmite of the mass of natural graphite is added, and the ball milling is continued at a speed of 400r / min for 3h to obtain the ball mill material;

[0040] Wherein, the D50 of the boehmite is 100 nm;

[0041] The asphalt is selected from coal asphalt;

[0042] The obtained ball milled material was transferred to a carbonization furnace, and then argon gas was introduced to replace the air in the carbonization furnace, and then the material was continuously heated to 900°C at a rate of 4°C / min, and carbonized for 3 hours, and then cooled to room temperature with the furnace, and the material was discharged to obtain a carbonized material;

[0043] The obtained carbonized material is poured into a pulverizer for pulverization, and particles with a D50 of 100 nm are sieved out to obtain carbon-coated graphite;

[0044] Preparation of composite materials:

[0045] 4 parts of polytetrafluoroethylene resin, 8 parts of N-methylpyrrolidone, 25 parts of carbon-coated graphite, and 120 parts of modified artificial graphite were mixed and poured into a kneader. The kneading was continued for 6 hours at a speed of 220 r / min and a temperature of 65°C to obtain a kneaded material.

[0046] The obtained kneaded material is transferred to a carbonization furnace, argon is introduced into the furnace at a rate of 120L / min, and under argon protection, the temperature is raised to 720°C at a rate of 3°C / min. After carbonization for 2 hours, the material is cooled to room temperature with the furnace and discharged. The material in the carbonization furnace is transferred to a pulverizer for pulverization and sieved to obtain a composite material with a D50 of 15μm, that is, a composite material of modified artificial graphite and carbon-coated graphite.

[0047] Example 2

[0048] Artificial graphite modification:

[0049] Artificial graphite and water were mixed in a mass ratio of 1:8, and then 2% of the mass of artificial graphite sodium lignin sulfonate was added, followed by constant temperature ultrasonic dispersion for 2.5 hours at a temperature of 85°C and an ultrasonic frequency of 190kHz to obtain a dispersion;

[0050] The obtained dispersion was transferred into a reactor, and an acidic hydrogen peroxide solution with a mass of 1 times that of the dispersion was added into the reactor, and then the reactor was closed, and the reaction was stirred at a constant temperature of 72° C. and a stirring speed of 900 r / min for 5 hours, and then the filter cake was collected and washed with deionized water until the washing liquid was neutral, and the washed filter cake was transferred into a drying oven and dried to constant weight at a temperature of 100° C. to obtain a dry filter cake;

[0051] The dried filter cake was manually ground in a mortar for 20 min, and then sieved to separate particles with a D50 of 8 μm to obtain modified artificial graphite;

[0052] Wherein, in the acidic hydrogen peroxide solution, the mass fraction of sulfuric acid is 12%, and the mass fraction of hydrogen peroxide is 22%;

[0053] Carbon coating of natural graphite:

[0054] The three raw materials of natural graphite, asphalt and microcrystalline cellulose were weighed according to the mass ratio of 85:11:2, poured into a ball mill, and then added with boehmite of 0.7% of the mass of natural graphite, and the ball milling was continued at a speed of 400 r / min for 3 hours to obtain a ball mill material;

[0055] Wherein, the D50 of the boehmite is 120nm;

[0056] The asphalt is selected from petroleum asphalt;

[0057] The obtained ball milled material was transferred to a carbonization furnace, and then argon gas was introduced to replace the air in the carbonization furnace, and then the material was continuously heated to 980°C at a rate of 5°C / min, and carbonized for 4 hours, and then cooled to room temperature with the furnace, and the material was discharged to obtain a carbonized material;

[0058] The obtained carbonized material is poured into a pulverizer for pulverization, and particles with a D50 of 200 nm are sieved out to obtain carbon-coated graphite;

[0059] Preparation of composite materials:

[0060] 5 parts of polytetrafluoroethylene resin, 9 parts of N-methylpyrrolidone, 28 parts of carbon-coated graphite, and 140 parts of modified artificial graphite were mixed and poured into a kneader. The kneading was continued for 7 hours at a speed of 240 r / min and a temperature of 68°C to obtain a kneaded material.

[0061] The obtained kneaded material is transferred to a carbonization furnace, argon is introduced into the furnace at a rate of 120L / min, and under argon protection, the temperature is raised to 760°C at a rate of 4°C / min. After carbonization for 3 hours, the material is cooled to room temperature with the furnace and discharged. The material in the carbonization furnace is transferred to a pulverizer for pulverization and sieved to obtain a composite material with a D50 of 18μm, that is, a composite material of modified artificial graphite and carbon-coated graphite.

[0062] Example 3

[0063] Artificial graphite modification:

[0064] Artificial graphite and water were mixed in a mass ratio of 1:8, and then 3% of the mass of artificial graphite sodium lignin sulfonate was added, followed by constant temperature ultrasonic dispersion for 3 hours at a temperature of 90°C and an ultrasonic frequency of 200kHz to obtain a dispersion;

[0065] The obtained dispersion was transferred into a reactor, and an acidic hydrogen peroxide solution of 1.2 times the mass of the dispersion was added into the reactor, and then the reactor was closed, and the reaction was stirred at a constant temperature of 75°C and a stirring speed of 1000 r / min for 6 hours, and then the filter cake was collected and washed with deionized water until the washing liquid was neutral, and the washed filter cake was transferred into a drying oven and dried to constant weight at a temperature of 100°C to obtain a dry filter cake;

[0066] The dried filter cake was manually ground in a mortar for 20 min, and then sieved to separate particles with a D50 of 10 μm to obtain modified artificial graphite;

[0067] Wherein, in the acidic hydrogen peroxide solution, the mass fraction of sulfuric acid is 15%, and the mass fraction of hydrogen peroxide is 25%;

[0068] Carbon coating of natural graphite:

[0069] The three raw materials of natural graphite, asphalt and microcrystalline cellulose are weighed according to the mass ratio of 90:12:3, poured into a ball mill, and then added with boehmite of 0.8% of the mass of natural graphite, and the ball milling is continued for 3 hours at a speed of 400 r / min to obtain a ball mill material;

[0070] Wherein, the D50 of the boehmite is 150nm;

[0071] The asphalt is selected from coal asphalt;

[0072] The obtained ball milled material was transferred to a carbonization furnace, and then argon gas was introduced to replace the air in the carbonization furnace, and then the material was continuously heated to 1000°C at a rate of 6°C / min, and carbonized for 5 hours, and then cooled to room temperature with the furnace, and the material was discharged to obtain a carbonized material;

[0073] The obtained carbonized material is poured into a pulverizer for pulverization, and particles with a D50 of 300 nm are sieved out to obtain carbon-coated graphite;

[0074] Preparation of composite materials:

[0075] According to weight percentage, 6 parts of polytetrafluoroethylene resin, 10 parts of N-methylpyrrolidone, 30 parts of carbon-coated graphite, and 150 parts of modified artificial graphite are mixed and poured into a kneader. After continuous shearing and kneading for 8 hours at a speed of 260 r / min and a temperature of 70°C, a kneaded material is obtained;

[0076] The obtained kneaded material is transferred to a carbonization furnace, argon is introduced into the furnace at a rate of 120L / min, and under argon protection, the temperature is raised to 800°C at a rate of 5°C / min. After carbonization for 4 hours, the material is cooled to room temperature with the furnace and discharged. The material in the carbonization furnace is transferred to a pulverizer for pulverization and sieved to obtain a composite material with a D50 of 20μm, that is, a composite material of modified artificial graphite and carbon-coated graphite.

[0077] Example 4

[0078] Compared with Example 1, this embodiment is different in that:

[0079] During the modification process of artificial graphite, sodium lignin sulfonate was not added, and the ultrasonic frequency was adjusted down from 180 kHz to 75 kHz, while the other conditions remained unchanged.

[0080] Example 5

[0081] Compared with Example 1, this embodiment is different in that:

[0082] An equal amount of alumina was used to replace boehmite, and the other conditions remained unchanged.

[0083] Example 6

[0084] Compared with Example 1, this embodiment is different in that:

[0085] No boehmite was added and the other conditions remained unchanged.

[0086] Comparative Example 1

[0087] Compared with Example 1, this comparative example has the following differences:

[0088] The artificial graphite was not modified and was directly used in the preparation of the composite material, and the other conditions remained unchanged.

[0089] Comparative Example 2

[0090] Compared with Example 1, this comparative example has the following differences:

[0091] Natural graphite was not treated with carbon coating and was directly used in the preparation of composite materials, and other conditions remained unchanged.

[0092] The performance tests were performed on the products obtained in Examples 1-6 and Comparative Examples 1-2. The specific test methods and test results are as follows:

[0093] Cycle performance test:

[0094] The products obtained in the above embodiments or comparative examples were used as negative electrode active materials, respectively. The negative electrode active material, conductive carbon black Super-P and carboxymethyl cellulose were mixed in a mass ratio of 94:3:3, and deionized water was added as a solvent. The mixture was stirred at a speed of 300 r / min for 12 h to prepare a negative electrode slurry. The negative electrode slurry was then scraped on the surface of the copper foil and dried to obtain a negative electrode sheet, which was then cut after rolling. The compaction density of the active material on the surface of the negative electrode sheet was controlled at 1.68 g / cm 3 ;

[0095] With lithium nickel cobalt manganese oxide (NCM523) as the positive electrode active material, the positive electrode active material, the conductive agent acetylene black and PVDF are mixed in a mass ratio of 95:3:2, and N-methylpyrrolidone is used as the solvent to prepare the positive electrode slurry, which is then coated on the surface of aluminum foil and dried, and then rolled and cut to obtain the positive electrode sheet. The compaction density of the active material on the surface of the positive electrode sheet is controlled at 3.75g / cm 3 ;

[0096] Use polyethylene film as the diaphragm;

[0097] In an argon atmosphere glove box, organic solvents ethylene carbonate (EC) / diethyl carbonate (DEC) / ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 1 / 1 / 1, and 1 mol / L LiPF6 lithium salt was added and dispersed evenly to obtain an electrolyte;

[0098] The prepared positive electrode sheet, negative electrode sheet and separator are made into corresponding electrode assemblies according to the Z-shaped stacking structure. The electrode assembly is vacuum dried at 90℃ for 12h, and then the positive and negative electrode tabs are ultrasonically welded. The positive electrode uses aluminum tabs and the negative electrode uses nickel tabs. The positive and negative electrode tabs are located on the same side of the electrode assembly. The electrode assembly after the tabs are welded is placed in an aluminum-plastic film of appropriate size for top and side sealing. The top and side sealing temperature is 145℃, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes static, hot and cold pressing, formation, shaping, capacity testing and other processes in sequence to obtain a battery cell.

[0099] The obtained single battery was charged at 0.5C current at 25°C until the charging voltage reached 4.25V, and then continued to charge at a constant voltage until the current reached 0.05C, at which time the charging was stopped, and it was considered fully charged; then the single battery was discharged at 1C current until the voltage reached 2.7V, at which time the discharging was stopped, and it was considered fully discharged;

[0100] The battery is fully charged and discharged until it decays to less than 80% of its initial capacity, which is considered the end of its life and the cycle life is obtained.

[0101] Dynamic performance test:

[0102] Capacity retention rate: A batch of batteries were prepared for this test using the above method, and the batch of batteries were tested using the Chenhua electrochemical workstation. They were charged to 4.2V at room temperature with a current of 0.5C, left for 5 minutes, and then discharged to 2.6V with 0.5C, and the discharge capacity was recorded. The same method was used to calculate the different charging rates of 1C, 2C, and 3C, and the discharge capacity was recorded. Capacity retention rate = discharge capacity of nC / discharge capacity of 0.5C, n = 0.5, 1, 2, 3.

[0103] The specific test results are shown in Table 1:

[0104] Table 1: Product cycle performance test results

[0105] Cycle life / cycle 1C retention rate / % 2C retention rate / % 3C retention rate / % Example 1 2567 99.0 98.1 96.2 Example 2 2578 99.2 98.4 96.6 Example 3 2611 99.1 98.2 96.2 Example 4 2512 98.5 97.1 94.9 Example 5 2480 97.2 95.5 92.9 Example 6 2410 96.6 94.1 91.1 Comparative Example 1 2234 95.5 91.9 88.0 Comparative Example 2 2150 95.2 91.5 87.7

[0106] It can be seen from the test results in Table 1 that the product obtained by the present invention has excellent cycle performance and has a relatively high capacity retention rate under high current charge and discharge conditions.

[0107] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A process for preparing a composite material of modified artificial graphite and carbon-coated graphite, characterized in that: The specific preparation process includes: Artificial graphite modification: After the artificial graphite is ultrasonically dispersed and exfoliated, an acidic hydrogen peroxide solution is added for oxidation to form oxygen-containing functional groups on the surface of the artificial graphite, and then particles with a D50 of 5-10 μm are screened out to obtain modified artificial graphite; Carbon coating of natural graphite: Natural graphite, asphalt and microcrystalline cellulose are blended, and 0.6-0.8% of boehmite by weight of the natural graphite is added, carbonized, crushed, and particles with a D50 of 100-300 nm are sieved to obtain carbon-coated graphite; The mass ratio of the natural graphite, the asphalt and the microcrystalline cellulose is (80-90): (10-12): (1-3); The D50 of the boehmite is 100-150nm; Composite material preparation: By weight, 4-6 parts of polytetrafluoroethylene resin, 8-10 parts of N-methylpyrrolidone, 25-30 parts of carbon-coated graphite, and 120-150 parts of modified artificial graphite are mixed, sheared and kneaded to obtain a kneaded material; The kneaded material is heated to 720-800°C in an oxygen-free environment for carbonization, and then crushed and sieved to obtain a composite material with a D50 of 15-20 μm.

2. The process for preparing a composite material of modified artificial graphite and carbon-coated graphite according to claim 1, characterized in that: The ultrasonic dispersion peeling comprises: Artificial graphite and water are mixed in a mass ratio of 1:8, and then 1-3% of the mass of artificial graphite sodium lignin sulfonate is added, followed by continuous ultrasonic dispersion for 2-3 hours at a temperature of 80-90°C and an ultrasonic frequency of 180-200kHz to obtain a dispersion.

3. The process for preparing a composite material of modified artificial graphite and carbon-coated graphite according to claim 2, characterized in that: The step of adding an acidic hydrogen peroxide solution for oxidation comprises: Add 0.8-1.2 times the mass of the dispersion liquid in an acidic hydrogen peroxide solution to the dispersion liquid, and then stir and react for 4-6 hours at a temperature of 70-75° C. and a stirring speed of 800-1000 r / min; Wherein, in the acidic hydrogen peroxide solution, the mass fraction of sulfuric acid is 10-15%, and the mass fraction of hydrogen peroxide is 20-25%.

4. The process for preparing a composite material of modified artificial graphite and carbon-coated graphite according to claim 1, characterized in that: The asphalt is selected from any one of coal asphalt and petroleum asphalt.

5. The process for preparing a composite material of modified artificial graphite and carbon-coated graphite according to claim 1, characterized in that: The shearing and kneading comprises: in a kneading machine, the rotation speed is 220-260r / min, the temperature is 65-70°C, and the shearing and kneading is continued for 6-8h.

6. A composite material of modified artificial graphite and carbon-coated graphite, characterized in that: The invention is prepared by the preparation process described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-capacity graphite material and preparation method as well as application thereof

    CN102659091A

  • Preparation process of composite material of artificial graphite and carbon-coated natural graphite

    CN117800335A

  • Carbon material, method for producing carbon material, method for producing negative electrode, and method for producing secondary battery

    WO2024117095A1